Pengaruh current ratio dan struktur modal terhadap return on equity - Hernawati, Euis; Muthmainnah, Muthmainnah; Ikhsan, Sugiyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
A good company's capital structure has an influence on the entity's financial condition, which basically will also encourage the entity's ability to earn profits. This study aims to determine the effect of current ratio and capital structure as independent variables, both simultaneously and partially, on return on equity as the dependent variable. The object of this study is PT Unilever Indonesia's financial statements for the period 2015–2019. This empirical testing activity uses causal research through a quantitative approach. The data analysis used was multiple linear regression analysis, and the research sample technique used purposive sampling. The results and conclusions in the study obtained simultaneously indicate that the independent variables, namely current ratio and capital structure, have a significant influence on return on equity as the dependent variable. Meanwhile, partially based on the results of the empirical test, the results show that the current ratio does not have a significant effect on return on equity, while capital structure has a significant effect on return on equity.